Apropos Aesthetic Autonomy - Sallis, Friedemann (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2003)
The present contribution to the Colloquy takes issue with problematic positions on aesthetic autonomy in music, which have appeared over the past couple of years in the pages of this journal. The tone is frank, the intention is constructive and the point is to engage in an exchange of ideas with colleagues who may have different points of view on these matters.